Pelaksanaan Jam Diniyah di MI Terpadu Mutiara Assyifa Kota Bengkulu dalam Pembentukan Karakter Keagamaan Siswa - Shella Diandana; Juwita Anggraini; Marisa Rachelia Putri; Mona Nurrahma (Yayasan Darusssalam Bengkulu, 2025)
This study aims to examine in depth the implementation of the Diniyah hour program at MI Terpadu Mutiara Assyifa, Bengkulu City and its contribution to the formation of students' religious character. In the context of Islamic education, Diniyah hours are part of a learning strategy based on religious values ​​that play an important role in forming students' religious and noble personalities. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through direct observation of the implementation process, interviews with teachers and principals, as well as administrative documentation and teaching materials used. The results of the study indicate that the Diniyah hour program is implemented in a scheduled and systematic manner every morning before general lessons begin. The materials taught include reading and writing the Qur'an, aqidah-akhlak, basic fiqh, memorizing daily prayers, and the history of Islamic culture. This program has succeeded in forming students' religious habits such as discipline in praying, praying before and after studying, and showing mutual respect between friends. The obstacles faced include lack of time, limited learning media, and variations in students' learning interests. However, the school has made various innovations in teaching such as the use of audio-visual media and a fun learning approach. This program has proven effective in forming students' religious character from an early age and needs to be continuously developed.